2021
DOI: 10.1186/s12974-021-02277-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphoproteomic landscape evoked in response to type I interferon in the brain and in glial cells

Abstract: Background Type I interferons (IFN-I) are key responders to central nervous system infection and injury and are also increased in common neurodegenerative diseases. Their effects are primarily mediated via transcriptional regulation of several hundred interferon-regulated genes. In addition, IFN-I activate several kinases including members of the MAPK and PI3K families. Yet, how changes to the global protein phosphoproteome contribute to the cellular response to IFN-I is unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…First, IFN‐I treatment leads to the upregulation of ISGs, so a single ISG, or a set of ISGs, may be responsible for the increase in seeded tau aggregation. Notably, IFN‐I induces widespread phosphorylation changes in the murine brain, driven by kinase families known to phosphorylate tau 37 . Further, IFN‐I, either through ISGs or JAK/STAT signaling directly, may affect the degradation of tau assemblies entering the cell or following their formation in the seeded tau aggregation process.…”
Section: Discussionmentioning
confidence: 99%
“…First, IFN‐I treatment leads to the upregulation of ISGs, so a single ISG, or a set of ISGs, may be responsible for the increase in seeded tau aggregation. Notably, IFN‐I induces widespread phosphorylation changes in the murine brain, driven by kinase families known to phosphorylate tau 37 . Further, IFN‐I, either through ISGs or JAK/STAT signaling directly, may affect the degradation of tau assemblies entering the cell or following their formation in the seeded tau aggregation process.…”
Section: Discussionmentioning
confidence: 99%
“…The early STAT1 homodimer response is recapitulated by its phosphorylation pattern: reanalysing data from He et al 35 , we observed that STAT1 becomes phosphorylated at sites T699 and Y701, almost immediately upon IFN-y/LPS stimulation of THP1 derived macrophages, followed by a gradual decrease over time ( Extended Data Figure 6g ). Indeed, phosphorylation of these sites is known to be induced by IFN signaling and trigger accumulation in the nucleus and activation of STAT1 DNA binding activity 36,37 . In contrast to this, the gradual increase in STAT2 and IRF9 activity is reflected by a delayed but sustained increase in the phosphorylation of IRF9 at sites S131 and S253 ( Extended Data Figure 6h ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent RNA-seq analysis between young and aged traumatic brain injury mice reported age-related upregulation of cGAS and type I IFN, which appears to be closely related with microglia-mediated neuroinflammation ( Barrett et al, 2021 ). Except for microglia, astrocytes are the other key players in response to type I IFN according to a proteomics study ( Viengkhou et al, 2021 ). Of interest, previous studies have reported that tPA-induced ICH and traumatic brain injury alter the type I IFN response and STING-mediated type I IFN response, respectively, in mice, thus exacerbating neuroinflammation ( Abdullah et al, 2018 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%